2002
DOI: 10.1194/jlr.m200145-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

ApoC-III gene polymorphisms and risk of coronary artery disease

Abstract: Several polymorphisms in the apolipoprotein C-III (apoC-III) gene have been associated with hypertriglyceridemia, but the link with coronary artery disease risk is still controversial. In particular, apoC-III promoter sequence variants in the insulin responsive element (IRE), constitutively resistant to downregulation by insulin, have never been investigated in this connection. We studied a total of 800 patients, 549 of whom had angiographically documented coronary atherosclerosis, whereas 251 had normal coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 36 publications
2
66
0
2
Order By: Relevance
“…The details of the study have been reported previously (16 ). Briefly, we selected a total of 848 unrelated adult patients of both sexes who were recruited consecutively from those referred to the Institute of Cardiovascular Surgery or to the Cardiovascular-Hypertension Unit of the Department of Internal Medicine of the University of Verona in Italy and underwent coronary angiography (the Verona Heart Project).…”
Section: Patients and Methods Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the study have been reported previously (16 ). Briefly, we selected a total of 848 unrelated adult patients of both sexes who were recruited consecutively from those referred to the Institute of Cardiovascular Surgery or to the Cardiovascular-Hypertension Unit of the Department of Internal Medicine of the University of Verona in Italy and underwent coronary angiography (the Verona Heart Project).…”
Section: Patients and Methods Study Populationmentioning
confidence: 99%
“…Serum lipids and the other common biochemical indices were measured as described previously (16 ). Apo A1, apo B, and apo E were measured by commercially available nephelometric immunoassays; antisera, calibrators, and the BNII nephelometer were from Dade Behring.…”
Section: Biochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In plasma, apoC-III resides on both TAGrich lipoproteins and HDLs. Overproduction of apoC-III and TAG-rich lipoproteins is a common feature in patients with hypertriglyceridemia (10,11). apoC-III also stimulates hepatic synthesis and secretion of VLDLs (12,13).…”
mentioning
confidence: 99%
“…(9)(10)(11) Olivieri and co-workers, (5) identifi ed apoCIII polymorphisms that are believed to play an important role in the metabolism of circulating triglyceride rich lipoproteins. Several variant alleles of the apoCIII gene have been investigated as possible genetic markers of hypertriglyceridaemia.…”
mentioning
confidence: 99%